2019
DOI: 10.1085/jgp.201912342
|View full text |Cite
|
Sign up to set email alerts
|

Tracking nitroxyl-derived posttranslational modifications of phospholamban in cardiac myocytes

Abstract: Mundiña-Weilenmann and Mattiazzi examine new work revealing the mechanism by which nitroxide modifies uptake of Ca2+ into the SR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 43 publications
0
1
0
Order By: Relevance
“…The mechanism by which azanone affects the heart is a matter of intense research. It has been proposed that HNO donors enhance cardiac contractility, by targeting the regulatory protein phospholamban [ 74 , 75 ]. Keceli et al found that HNO reacts with Cys-41 and Cys-46 via the formation of the intramolecular disulfide bond, which forces conformational changes in the protein and enhances cardiac function as a result [ 74 ].…”
Section: Introductionmentioning
confidence: 99%
“…The mechanism by which azanone affects the heart is a matter of intense research. It has been proposed that HNO donors enhance cardiac contractility, by targeting the regulatory protein phospholamban [ 74 , 75 ]. Keceli et al found that HNO reacts with Cys-41 and Cys-46 via the formation of the intramolecular disulfide bond, which forces conformational changes in the protein and enhances cardiac function as a result [ 74 ].…”
Section: Introductionmentioning
confidence: 99%